The Influence Of Promotion And Quality Of Tourism Products On Tourist Satisfaction Mediated By Brand Image In Banyumulek Tourism Village, West Lombok District - Sakirin Sakirin; Hendrajaya Hendrajaya; Wahyu Tri Astuti (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The purpose of this study was to analyze and explain the effect of promotion and quality of tourism products on tourist satisfaction in mediating brand image in Banyumelek Village, Kediri District, West Lombok. This research is an inferential research emphasizing the analysis of numerical data processed using statistical methods, namely examining the factors that occur and the results of the research will describe the effect of promotion and the quality of tourism products on ourist.atisfaction in mediating brand image in Banyumelek Village, Kediri District, West Lombok. The sample of this study took tourists who came to visit the Banyumulek Tourism Village took 100 tourists who came to visit the Banyumulek Tourism Village. The data collection technique used a questionnaire and the data was tested and analyzed using multiple linear regression with the SPSS version 20 program. Based on the results of research data analysis it can be concluded that: (1). Positive and significant influence of promotion on brand image (2). Positive and significant influence of the quality of tourism products on brand image. (3). Positive and significant influence of promotions on satisfaction (4). Positive and significant influence of the quality of Widsata products on satisfaction. (5). Positive and significant influence of brand image on tourist satisfaction. (6). the effect of promotion on tourist satisfaction is mediated by brand image. (7). There is no influence of the quality of tourism products on tourist satisfaction mediated by brand image in Banyumulek Tourism Village.